Utilization of PowerPoint and YouTube as Digital-Based Learning Media: Literature Review - Iskandar, Ranu; Syafei, M. Hilman Gumelar; Bahatmaka, Aldias; Hidayat, Hanif; Huda, Khoirul (Peneliti.net, 2023)
Learning media is one of the most essential tools in the learning process in the classroom. Learning media can help students understand the material presented more effectively and clearly. Learning media is continuously experiencing significant development, especially in the fourth industrial revolution era. With the fourth industrial and internet technology course, teachers and educators must also know the latest products regarding learning media that can be used. Among the currently commonly used media are Microsoft Office PowerPoint and YouTube. This study aims to discuss two digital-based learning media, i.e., YouTube and Microsoft PowerPoint. The study is conducted through a literature review of several available and current references. It was found that Microsoft PowerPoint and YouTube are effective media for learning and can help students understand better.